The proportion of inadequately ICPC2 signs and symptoms coded as a chronic disease in general practice/family medicine: a preliminary study in Central Portugal - Pinto Coelho, Joana (2023)
Objective: To identify ICPC-2 chapters “signs and symptoms” incorrectly classified as active and chronic ones, its proportion and main involved chapters. Methods: An observational, cross-sectional, quasi-random, exploratory study was carried out using data collected from consultations every Tuesday, Wednesday, and Friday during August of 2021, in the consultations of two General Practice/Family Doctors in Primary Care Health Unit of the Portuguese National Health Service. A descriptive analysis of the list of active problems of the users and recording of the classifications considered inappropriate was performed. Results: The evaluated population consisted of 123 patients, 52,8% female, mean sample age being of 53,3±22,4 years. For 45,5% of the patients there were chronic misclassifications, with 8,2% misclassifications. The musculoskeletal (16,3%), psychological (7,3%) and the female genital, circulatory and general and nonspecific (all with 5,7%) chapters were the most frequent. There were no significant difference by gender and age, but the greater the number of total classifications, the greater the number of misplaced classifications. Discussion: The results may have a negative impact on patient follow-up, communication between physicians and increased time spent in consultations, due to the lack of updating the list of problems, and decreased credibility of records for investigation. The high prevalence of musculoskeletal signs and symptoms can lead to the resolution of these problems as chronic. The COVID-19 pandemic can be associated with a greater number of transient symptoms but classified as active. A large number of active issues can affect appropriate classification. Conclusion: It is important to periodically update the list of problems, invest in the training of family doctors in ICPC-2 use and frequently evaluate the classifications. Further validation studies of classified information in electronic record systems are needed.